Teaching Reading And Counting In Salah: Experiences Of Muslim Caregivers Of Down Syndrome Children In Selangor - binti Abdul Rahman, Amira; Suraya Mohamad, Fitri (International Journal of Engineering and Technology, 2018)
Children born with Down Syndrome face difficulty in reciting daily prayers as they are born with cognitive disabilities which affect the process of acquiring reading and counting skills.Â Although in Islam, these children are not required to perform Salah, the strong cultural family norms among Malay Muslims in Malaysia create an expectation of them to participate in Salah as part of their daily routines. This study examines the experiences in teaching Down Syndrome children how to read and count in Salah among Muslim family caregivers in the state of Selangor, Malaysia. The study also investigates best practices to facilitate a Down Syndrome child to perform daily religious prayers that involves the skills of reading and counting. Case study method is deployed to examine responses from three informants who voluntarily participated in this study. The study uses non-probability sampling to acquire accurate and realistic conceptions from caregivers who are actively working with their respective Down Syndrome children. Findings from the study revealed a high tendency among caregivers to use repetition in the learning process, and to create an environment where the Down Syndrome children can imitate the actions done and words spoken when performing the Salah. The use of rewards is also found to be useful and effective to motivate and encourage Down Syndrome children to learn to cognitive tasks for Salah. Â Â